Comprehensive CT Evaluation in Acute Ischemic Stroke: Impact on Diagnosis and Treatment Decisions - Askell Löve; Roger Siemund; Gunnar Andsberg; Mats Cronqvist; Stig Holtås; Isabella Björkman-Burtscher (Stroke Research and Treatment)
Background. With modern CT imaging a comprehensive overview of cerebral macro- and microcirculation can be obtained within minutes in acute ischemic stroke. This opens for patient stratification and individualized treatment. Methods. Four patients with acute ischemic stroke of different aetiologies and/or treatments were chosen for illustration of the comprehensive CT protocol and its value in subsequent treatment decisions. The patients were clinically evaluated according to the NIHSS-scale, examined with the comprehensive CT protocol including both CT angiography and CT perfusion, and followed up by MRI. Results. The comprehensive CT examination protocol increased the examination time but did not delay treatment initiation. In some cases CT angiography revealed the cause of stroke while CT perfusion located and graded the perfusion defect with reasonable accuracy, confirmed by follow-up MR-diffusion. In the presented cases findings of the comprehensive CT examination influenced the treatment strategy. Conclusions. The comprehensive CT examination is a fast and safe method allowing accurate diagnosis and making way for individualized treatment in acute ischemic stroke.